Post-Umrah Meaning-Making among Chinese Indonesian Muslim Converts: An Interpretive Qualitative Study - Indaturrohmah, Nur; Muhajarah, Kurnia (Jurnal Sosiologi Agama Indonesia (JSAI), 2026)
Religious conversion involves ongoing negotiations of identity, social relationships, religious practice, and life meaning. Although previous studies have examined Chinese Indonesian converts and the spiritual dimensions of Umrah, little is known about how converts retrospectively connect pilgrimage experiences with post-conversion difficulties and everyday life. This study examines how Chinese Indonesian Muslim converts interpreted significant experiences during Umrah and related them to reported changes in life meaning. It used a qualitative descriptive design with an interpretive orientation. Five participants were recruited through purposive and snowball sampling. Data were collected from January to March 2026 through three synchronous online semi-structured interviews and two written responses based on the same open-ended guide and were then analyzed thematically. Two themes were identified. First, participants interpreted encounters at sacred sites through awe, crying, calmness, surrender, perceived closeness to God, and perceived divine assistance. Second, they connected these experiences with greater acceptance of adversity, religious confidence, continued religious learning, and changes in worship or everyday conduct. These accounts were embedded in earlier family disagreement, social pressure, and identity negotiation, and their depth varied across participants. Umrah therefore appeared as a symbolic and emotional reference point within continuing meaning-making rather than as an independent cause of psychological recovery or uniform long-term transformation. The study contributes an interpretive account of how pilgrimage memories, conversion histories, religious identity, and social relationships intersect in the post-conversion narratives of Chinese Indonesian Muslims.